2017
DOI: 10.1017/s1751731117000052
|View full text |Cite
|
Sign up to set email alerts
|

Relative emissions intensity of dairy production systems: employing different functional units in life-cycle assessment

Abstract: This study aimed to assess the merit and suitability of individual functional units (FU) in expressing greenhouse gas emissions intensity in different dairy production systems. An FU provides a clearly defined and measurable reference to which input and output data are normalised. This enables the results from life-cycle assessment (LCA) of different systems to be treated as functionally equivalent. Although the methodological framework of LCA has been standardised, selection of an appropriate FU remains ultim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
1
12
0
3
Order By: Relevance
“…However, differences in LCA methodology, allocation methods (for milk and meat) or functional unit hinder comparability (Baldini et al, 2017) and a meta-analysis of 30 published LCA's with 87 carbon footprints from pasture, mixed, and confinement dairy systems found no average footprint differences per kg of FPCM (Lorenz et al, 2019). Choice of functional unit is also important when expressing results from LCA studies assessing environmental impacts arising from differing dairy systems and when considering effects of intensification (Ross et al, 2017, Salou et al, 2017. As far as the authors are aware, allocation methods assessing feed components and their effect on dairy system carbon footprints are not available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…However, differences in LCA methodology, allocation methods (for milk and meat) or functional unit hinder comparability (Baldini et al, 2017) and a meta-analysis of 30 published LCA's with 87 carbon footprints from pasture, mixed, and confinement dairy systems found no average footprint differences per kg of FPCM (Lorenz et al, 2019). Choice of functional unit is also important when expressing results from LCA studies assessing environmental impacts arising from differing dairy systems and when considering effects of intensification (Ross et al, 2017, Salou et al, 2017. As far as the authors are aware, allocation methods assessing feed components and their effect on dairy system carbon footprints are not available in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recent increases in TMR‐fed cattle have contributed to the global rise in milk and meat production, but may also be linked to the rise in atmospheric methane emissions (Thornton, Jones, Ericksen, & Challinor, ; Wollenberg et al., ). Life cycle assessments are used to assess the emissions’ intensities of different livestock management systems; however, these assessments require many field measurements to parameterize the models (Ross, Topp, Ennos, & Chagunda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although gains in livestock N use efficiency and productivity normally contributed to the reduction of GHG emissions on a product basis, they were translated into higher potential environmental impacts from a land basis perspective. Changing outcomes with different functional units was also found by Ross et al (2017) who reported contrasting results when comparing the impacts of milk production on the basis of fat-and-protein-corrected milk yield and another on the basis of land unit. Our results are supported by literature on the need to account for impacts in a multi-metric approach because of mixed effects.…”
Section: Discussionmentioning
confidence: 68%
“…Although this statement is common sense in a great part of the literature, the question of efficiency is actually multifaceted. Ross et al (2017) reported that the environmental efficiency of dairy systems depends largely on the functional unit to which impacts are referenced: The same system had lower and higher emissions with a change from productto land-based functional unit, respectively. This highlights the need to account for impacts attributed to both the unit of produce (e.g.…”
Section: Introductionmentioning
confidence: 99%